La raccolta e la distribuzione dell'acqua a Ventotene in età romana - De Rossi, Giovanni Maria (Ricerche archeologiche nell'isola di Ventotene, 2019)
This volume, written by the Director of the Historical-Archaeological museum at Ventotene island, is divided into two parts: the first examines the topographical and technical problem of the water supply on the island, which essentially has no springs; the second analyses the individual components of the water supply system built by the Romans